PENGARUH SUSUNAN GENETIKA HASIL PERSILANGAN PUYUH (Coturnix-coturnix japonica) ASAL TIGA DAERAH (BENGKULU, PADANG, DAN YOGYAKARTA) TERHADAP KUALITAS KARKAS PUYUH JANTAN EFFECTS OF GENETIC COMPOSITION RESULTED FROM QUAIL (Coturnix-coturnic japonica) CROSSES FROM THREE PROVINCES (BENGKULU, PADANG, AND YOGYAKARTA) ON QUALITY OF MALE QUAILS CARCASS - , Kususiyah; Kaharuddin, Desia (Pembangunan Pedesaan, 2006)
An experiment was conducted to examine the effects of genetic composition of quails (Coturnix-coturnic japonica) resulted from crosses among quails originated from three provinces (Bengkulu, Padang, and Yogyakarta) on quality of male quails carcass. Genetic compositions were used as treatments, including P 1 (50% Bengkulu, 25% Padang, 25% Yogyakarta), P (50% Padang, 25% Bengkulu, 2 25% Yogyakarta), P (50% Yogyakarta, 25% Bengkulu, 25% Padang), P (100% 3 4 Bengkulu), P (100% Padang), P (100% Yogyakarta). Treatments with 292 5 6 unsexed day old quails were arranged in a Completely Randomized Design with seven replicates. Results demonstrated that genetic compositions affected body weight, carcass weight, breast length and wide, and meat bone ratio (P